Imaging the CarbFix2 Reinjection Reservoir at Hellisheiði, Iceland, with Body-wave Seismic Interferometry - Hassing, S.H.W. (author); Draganov, D.S. (author); Barnhoorn, A. (author); Janssen, M. (author) (Second EAGE Conference on Near Surface in Latin America, 2022)
In July 2021, passive seismic data has been recorded on a network of geophones at the CarbFix2 injection site at Hellisheiði, Iceland. This data is processed using seismic interferometry to get an image of the injection reservoir. The data is split up into noise panels. Panels dominated by body-wave energy are selected using an illumination analysis. In panels where the dominant event has a (near) vertical incidence, each trace is autocorrelated to get a zero-offset section. In panels where the dominant event is recognized as a body-wave event, all the traces are crosscorrelated, obtaining virtual common-shot gathers. This is processed with a reflection-seismology workflow to obtain a stacked section. Comparing the two final sections shows that similar reflectors are imaged. The zero-offset section shows a higher frequency content, while the stacked section shows more continuous reflectors. Comparison with a local geological model shows that the results are plausible, but that a better interpretation has to wait for more results of the same survey to be processed. Green Open Access added to TU Delft Institutional Repository ‘You share, we take care!’ – Taverne project https://www.openaccess.nl/en/you-share-we-take-care Otherwise as indicated in the copyright section: the publisher is the copyright holder of this work and the author uses the Dutch legislation to make this work public. Applied Geophysics and Petrophysics